Atribut Mutu Keripik Pisang Masak dengan Menggunakan Metode Importance Performance Analysis (IPA) - Citra Resmi Hayuningtyas; Bambang Herry Purnomo; Nurhayati Nurhayati (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2022)
The food processing industry currently produces various kinds of products with local food brands. In Lumajang Regency, the availability of banana var. Mas Kirana (Musa acuminate 'lady Finger') is very abundant so that it provides significant business opportunities. This study determined the quality attributes of ripe banana chips from SMEs in Lumajang Regency. Questionnaires were distributed to 100 respondents. The results of the questionnaire were processed using the Importance Performance Analysis (IPA) method. The results showed that the quality attributes of ripe banana chips based on the IPA method were ease of breaking, taste stability, packaging information, packaging safety, and shelf life. The key attributes of the